2009
DOI: 10.1097/eja.0b013e328319c153
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of combined spinal epidural vs. spinal anaesthesia for elective caesarean section: vasopressor requirements and cardiovascular changes

Abstract: CSEA placement appears to offer no haemodynamic benefits compared with SSSA when the same dose of local anaesthetic is administered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…However, use of smaller doses decreases the duration of anaesthesia and may necessitate the use of a combined spinal-epidural (CSE) technique [9]. Although it has previously been proposed that the CSE technique itself may be associated with higher blocks versus single-shot spinal anaesthesia using equivalent doses, this finding was not reproduced in two recent studies [10,11].…”
Section: Risk Factorsmentioning
confidence: 99%
“…However, use of smaller doses decreases the duration of anaesthesia and may necessitate the use of a combined spinal-epidural (CSE) technique [9]. Although it has previously been proposed that the CSE technique itself may be associated with higher blocks versus single-shot spinal anaesthesia using equivalent doses, this finding was not reproduced in two recent studies [10,11].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Numerous previous studies have confirmed the benefits of spinal anesthesia for cesarean section in comparison to general anesthesia. The results of these studies indicate greater safety for mother and child, lower likelihood of complications, less blood loss, and better mother and baby survival [10][11][12][13][14][15][16] . However, recent developments in pain treatment are more commonly investigated for the occurrence of chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the results of the present analysis, Horstman et al also demonstrated a similar blockade associated with CSEA and SSSA among 30 parturients (18–45 years old) who underwent elective cesarean delivery [17], and they also showed no significant differences in median pinprick sensory block height (T4 [T4-2] and T3 [T4-1]) or cerebrospinal fluid pressures. In addition, Macfarlane et al showed CSEA placement was not associated with hemodynamic advantages when compared to SSSA, even when the same dose of local anesthetic agent was administered [18]. In their study, hyperbaric bupivacaine (12.5 mg) and diamorphine (0.3 mg) were administered intrathecally via CSEA or SSSA in 70 women who underwent cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%